Internalisasi Nilai Disiplin Kewarganegaraan Melalui Mata Pelajaran Pendidikan Pancasila Bagi Murid Di SMP Negeri 6 Banjarmasin - Muhammad Luthfie; Sarbaini Sarbaini; Alex Alex (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the internalization of civic discipline values through Pancasila Education by identifying the factors contributing to low student discipline and examining the internalization process. This study employed a qualitative approach, with data collected through observation, interviews, and documentation. The informants consisted of a Pancasila Education teacher, the Vice Principal for Student Affairs, and seven students selected through purposive sampling. Data were analyzed through data reduction, data display, and conclusion drawing. The findings reveal that low student discipline is influenced by internal factors, including low self-awareness, procrastination habits, and weak time management, as well as external factors such as limited parental supervision and peer influence. The internalization process is implemented through planning, implementation, and evaluation stages, integrated with habituation, discussions, case studies, role modeling, and reinforcement through school programs.